Penciptaan Tari Hindu Dusun Laman Dalam Simbol Budaya Tradisi Tunggu Tubang Sebagai Interpretasi - Septiani, Nurhuda Sari (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study discusses the form of Hindu Dusun Laman dance in the cultural symbol of the Tunggu Tubang tradition in the Semende Tribe. The Tunggu Tubang tradition is a unique matrilineal system in South Sumatra, where women play an important role in the inheritance of property and the preservation of family values. The Hindu Dusun Laman dance, as one of the cultural elements, is a medium to express and maintain the symbolism of this tradition. Using the dance creation approach according to Alma Hawkins, the basis for this creation is carried out through the process of combining and developing traditional dance movements in accordance with the concept of the work. Through dance, a society can articulate their identity, history, and philosophy. Using a literature study method, this study analyzes various literature on dance, cultural symbolism, and social interpretation. The results of the study show that this dance has a deep meaning related to spirituality, obedience to ancestors, and the role of women in the social structure of the Semende Tribe. This study strengthens the understanding that dance is not only an art form, but also a means of maintaining and articulating cultural identity.